Effect of aliskiren on vascular remodelling in small retinal circulation. Issue 12 (December 2015) - Jumar, Agnes; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Schmidt, Stephanie; Harazny, Joanna M.; Schmieder, Roland E.
Abstract : Background: In hypertension, changes in small arterial structure are characterized by an increased wall-to-lumen ratio (WLR). These adaptive processes are modulated by the rennin–angiotensin system. It is unclear whether direct renin inhibitors exert protective effects on small arteries in hypertensive patients. Methods: In this double-blind, randomized, placebo-controlled study (www.clinicaltrials.gov: NCT01318395), 114 patients with primary hypertension were randomized to additional therapy with either placebo or aliskiren 300 mg for 8 weeks after 4 weeks of standardized open-label treatment with valsartan 320 mg (run-in phase). Parameter of arteriolar remodelling was WLR of retinal arterioles (80 – 140 μm) assessed noninvasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany). In addition, pulse wave analysis (SphygmoCor, AtCor Medical, Australia) and pulse pressure (PP) amplification were determined. Results: In the whole study population, no clear effect of additional therapy with aliskiren on vascular parameters was documented. When analyses were restricted to patients with vascular remodelling, defined by a median of WLR more than 0.3326 ( n  = 57), WLR was reduced after 8 weeks by the treatment with aliskiren compared with placebo (–0.044 ± 0.07 versus 0.0043 ± 0.07, P  = 0.015). Consistently, after 8 weeks of on-top treatment with aliskiren, there was an improvement of PP amplification compared with placebo (0.025 ± 0.07 versus -0.034 ± 0.08, P  = 0.013), indicative of less stiff arteries in the peripheral circulation. Conclusion: Thus, our data indicate that treatment with aliskiren, given on top of valsartan therapy, improves altered vascular remodelling in hypertensive patients.